LEGAL INSTRUMENTS FOR ANTI-RAIDING IN THE BUSINESS SPHERE - Sukhatskyi, Roman (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: on the basis of the study and analysis of the current legislation of Ukraine, international legal documents, the practice of their implementation, as well as the generalization of scientific works, to determine the essence and development trends of raiding in Ukraine, the administrative, legal and organizational principles of the activity of the authorized bodies of the state authorities of Ukraine in the sphere of combating raiding, as well as develop proposals and recommendations for their improvement. Research methods: the research is based on general scientific methods, methods of cognition, comparative analysis, objective truth, etc. Results: the theoretical meaning of the concept of "raiding" was determined, legal instruments for combating raiding in the business sphere were determined. Discussion: legal protection of business entities against unfriendly takeover (raiding). Economic competence of economic associations during self-defense against encroachments on their property. Legal regulation of enterprise information security. Structuring the information of the business entity. Definition of restricted information. Organization of information security of the enterprise as a component of protection against raiding. Legal regulation of the establishment of a private security service of an enterprise. Determination of the powers of the private security service. Protection of the interests of the business entity by the forces of the private security service. Protection of the company’s interests by the hired security service against raiders. Protection by state authorities of business entities from encroachment on their property.